2003
DOI: 10.1177/1043659603014003009
|View full text |Cite
|
Sign up to set email alerts
|

Community Readiness to Prevent Intimate Partner Violence in Bexar County, Texas

Abstract: The purpose of this article is to describe the Community Readiness Model implemented by the San Antonio Safe Family Coalition in Bexar County, Texas, a coordinated community response to prevent intimate partner violence. The project used a participatory action process to (a) determine the city's and county's stage of readiness to prevent intimate partner violence; (b) identify differences in the city and county by dividing the area into sectors for the assessment; (c) engage the community in determining the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 14 publications
0
28
0
Order By: Relevance
“…Since its inception in 1995 by Oetting et al, the model has been successfully used in a variety of international to local prevention and intervention programs dealing with drug and alcohol abuse Plested, Jumper-Thurman, Edwards, & Oetting, 1998), and reduction of HIV/AIDS (Kennedy et al, 2004). In addition, the model has been effectively used with social programs such as intimate partner violence prevention (Brackley et al, 2003;Han, 2003), breast cancer education (Lawsin, 2005), and needle exchange programs (Duynstee, 2001).…”
Section: Crmmentioning
confidence: 95%
“…Since its inception in 1995 by Oetting et al, the model has been successfully used in a variety of international to local prevention and intervention programs dealing with drug and alcohol abuse Plested, Jumper-Thurman, Edwards, & Oetting, 1998), and reduction of HIV/AIDS (Kennedy et al, 2004). In addition, the model has been effectively used with social programs such as intimate partner violence prevention (Brackley et al, 2003;Han, 2003), breast cancer education (Lawsin, 2005), and needle exchange programs (Duynstee, 2001).…”
Section: Crmmentioning
confidence: 95%
“…While other organizational change models exist (Lehman, Greener, & Simpson, 2002), this readiness model is a culturally sensitive and strengthbased tool (Jumper-Thurman, Edwards, Plested, & Oetting, 2003) that assesses a community's level of readiness and builds its capacity to successfully implement an initiative regardless of its current starting point. This model has been widely used both nationally and internationally for topics including: drug and alcohol prevention (Donnermeyer, Plested, Edwards, Oetting, & Littlethunder, 1997;Plested, Smitham, Jumper-Thurman, Oetting, & Edwards, 1999), cardiovascular disease (Peercy, Gray, Thurman, & Plested, 2010), intimate partner violence (Brackley et al, 2003;Han, 2003), smoking and tobacco use policy (York & Hahn, 2007), HIV/AIDS (Aboud, Huq, Larson, & Ottisova, 2010;McCoy, Malow, Edwards, Thurland, & Rosenberg, 2007;Plested, Edwards, & Thurman, 2007), breast cancer (Lawsin, Borrayo, Edwards, & Belloso, 2007), and head injury (Stallones, Gibbs-Long, Gabella, & Kakefuda, 2008). The model of community readiness provides a guided assessment and intervention process that leverages a community's strengths (e.g., culture, history, resources, level of problem awareness, readiness for change) to facilitate change (National Center for Community and Organizational Readiness, 2009;Plested, Jumper-Thurman, & Edwards, 2009).…”
Section: Community Readiness Modelmentioning
confidence: 99%
“…Over the past decade, research has shown that communities differ in their levels of readiness and that communities with higher levels of readiness are much more successful in planning, implementing, and sustaining community initiatives (e.g., Brackley et al, 2003;Logan, Williams, & Leukefeld, 2001;Plested, Smithman, Jumper-Thurman, Oetting, & Edwards, 1999). While some readiness frameworks include elements of community capacity, such as local leadership, knowledge, and access to resources (Edwards, JumperThurman, Plested, Oetting, & Swanson, 2000;Oetting et al, 1995;Oetting, Jumper-Thurman, Plested, & Edwards, 2001;Plested et al, 1999), we have chosen to distinguish readiness from capacity by framing readiness as the overall belief in the possibility of change and capacity as the local ability to implement change.…”
Section: Community Readiness For Changementioning
confidence: 99%